Outsourcing Love, Companionship, and Sex: Robot Acceptance and Concerns - I. Joyce Chang; Tim S. Welch; David Knox; Adriatik Likcani; Allison C. Tsay (Sexes, 2025)
Due to constantly evolving technology, a new challenge has entered the relationship landscape: the inclusion of robots as emotional and intimate partners. This article raises the question of the degree to which companionship and intimacy may be fulfilled by robots. Three hundred and fourteen undergraduates, the majority of whom were first- or second-year college students, responded to an online survey on robot acceptance. Factor analysis identified two constructs, which the authors labeled as simulated companionship (e.g., robots as companions/helpful assistants) and simulated intimacy (e.g., robots as intimate partners–emotional and sexual). Data analysis revealed a difference between companionship and intimacy regarding student robot acceptance for home use. Overall, there was greater acceptance of robots as companions than as intimate partners. Group differences for simulated companionship were found for gender, sexual values, commitment to religion, and sexual orientation. While robots may enhance various elements of human life, the data revealed the limits of outsourcing emotional intimacy, companionship, and sex to machines.